COVID-19 Infection in Chronic Myeloid Leukemia Patients Receiving Tyrosine Kinase Inhibitor in Makassar, Indonesia: A Six-Case Report and Literature Review - Tutik Harjianti; Fachruddin Benyamin; Rahmawati Minhajat; Sahyuddin Saleh; Dimas Bayu; Wahyudi Pababbari (Acta Medica Indonesiana)
Management of chronic myeloid leukemia (CML) in patients who are infected with COVID-19 is a challenging task due to disease-related or treatment-related factors that place such patients at a higher risk of complications. However, a low-infectivity-rate mechanism has been proposed by some researchers. In CML patients with COVID-19 infection, the most important treatment-related factor involves tyrosine kinase inhibitors (TKIs). In this case report, six patients with chronic-phase CML who experienced COVID-19 of mild–moderate severity all continued to receive TKI treatment for CML concurrently with COVID-19 treatment. All patients fully recovered. In the present study, we also review four other cases of COVID-19 infection in CML patients. Outcomes for TKI-treated CML patients who contract COVID-19 are influenced by many factors. Tyrosine kinase inhibitor therapy may benefit CML patients due to its antiviral effect, but the interaction between TKIs and drugs used for COVID-19 treatment requires careful monitoring. An individual approach is needed in every case.